A revision of the new world goblin spider genus Cinetomorpha Simon, 1892 revalidated from Gamasomorpha Karsch, 1881 (Araneae, Oonopidae, Oonopinae) - Ott, Ricardo; Ubick, Darrell; Bonaldo, Alexandre B.; Brescovit, Antonio D.; Harvey, Mark S. (Zootaxa, 2019)
The goblin spider genus Cinetomorpha Simon is removed from the synonymy of Gamasomorpha Karsch and treated as the senior synonym of Yumates Chamberlin and Lucetia Dumitresco & Georgesco. All 41 species occur only in the New World, and the genus is divided into four species groups: the simplex group, the puberula group, the patquiana group and the itabaiana group. The following species are transferred to Cinetomorpha: C. floridana (Banks), comb. nov., and C. sedata (Gertsch & Mulaik), comb. nov., from Opopaea; C. angela (Chamberlin), comb. nov., and C. nesophila (Chamberlin), comb. nov., from Yumates; and C. patquiana (Birabén) and C. platensis (Birabén), comb. nov., from Gamasomorpha. Gamasomorpha wasmanniae Mello-Leitão and Lucetia distincta Dumitresco & Georgesco are newly synonymized with C. simplex Simon. Two species currently in Gamasomorpha are transferred to Hexapopha Platnick & Berniker: H. brasiliana (Bristowe), comb. nov. and H. m-scripta (Birabén), comb. nov. The following 31 species are newly described: C. adaga Ott & Bonaldo (Brazil, Colombia, Ecuador and Peru); C. atlantica Ott & Brescovit (Brazil); C. baja Ott & Ubick (Mexico); C. bandolera Ott & Harvey (Mexico & USA); C. boraceia Ott & Brescovit (Argentina and Brazil); C. campana Ott & Harvey (Chile); C. central Ott & Brescovit (Brazil); C. chicote Ott & Bonaldo (Brazil, Colombia, Ecuador and Peru); C. concepcion Ott & Harvey (Chile); C. iguazu Ott & Brescovit (Argentina and Brazil); C. itabaiana Ott & Brescovit (Brazil); C. laguna Ott & Ubick (Mexico); C. lavras Ott & Brescovit (Brazil); C. longisetosa Ott & Harvey (Costa Rica and Brazil); C. lorenzo Ott & Harvey (Guatemala); C. loreto Ott & Bonaldo (Peru); C. nayarit Ott & Harvey (Mexico); C. orellana Ott & Bonaldo (Ecuador); C. pauferro Ott & Brescovit (Brazil); C. peluda Ott & Harvey (Chile); C. pinheiral Ott & Brescovit (Brazil); C. pocone Ott & Brescovit (Brazil); C. punctata Ott & Brescovit (Brazil); C. quillota Ott & Harvey (Chile); C. rinconada Ott & Harvey (Chile); C. santamaria Ott & Brescovit (Argentina); C. similis Ott & Brescovit (Brazil); C. sternalis Ott & Bonaldo (Brazil); C. sur Ott & Ubick (Mexico); C. waorani Ott & Bonaldo (Ecuador); and C. zero Ott & Harvey (Mexico to Venezuela).